The Preoperative Diagnostic Value of MRI and Otoneural Tests in Acoustic Neuroma - Dai, Qingqing; Zheng, Meijun; Chen, Qiurong; Zheng, Hong; Li, Bilan (Frontiers in Oncology, 2021)
Abstract Objectives: To determine the preoperative diagnostic accuracy of MRI and otoneural tests (ONT) for Acoustic Neuroma (AN) in a cohort of unselected patients with pontocerebellar angle tumors. To find a convenient way to screening out the potential asymptomatic AN patient earlier. Design: This diagnostic accuracy study was performed in a central hospital and included a consecutive sample of unilateral incipient pontocerebellar angle tumor patients referred for MRI and ONT before surgery. Different AN features of MRI and ONT were collected and concluded into preoperative diagnostic variables or variable combinations. Those of MRI and ONT are analyzed and compared with biopsy results by multivariable receiver operating characteristic (ROC) analysis. The early-stage group, the course of which is one year or less, was separately computed and compared. Results: Eighty-three subjects were collected from June 2013 to June 2019; sixty-two were confirmed AN postoperatively by biopsy, while others are not AN. The area under the curve (AUC) of MRI was 0.611, while the AUC of ONT was 0,708. In the early-stage group, the AUC of MRI was 0.539, and the AUC of ONT was 0.744. Conclusions: ONT was able to identify more subjects affected by unilateral incipient AN than MRI preoperatively. Given that ONT is a functional test for internal auditory canal nerves, it is an optimal screening test for AN patients because it provides more information than MRI for the further clinical plan. It is particularly noteworthy for identifying asymptomatic AN patients and for early stage. Therefore, it may help more patients from unnessesary surgery. Furthermore, an MRI follow-up is suggested if the patient was found alert in ONT..